Ergogenic aids: A review of basic science, performance, side effects, and status in sports - Tokish, J. M.; Kocher, M. S.; Hawkins, R. J. (The American Journal of Sports Medicine, 2004)
The use of drugs and supplements to enhance performance has become a part of mainstream athletics. Many team physicians and sports medicine practitioners are unfamiliar with the benefits and risks of these products and thus are unable to educate young athletes on this topic. In spite of numerous reports on the health risks of anabolic steroid use, 1 to 3 million Americans have used them. Human growth hormone has been tried by up to 5% of 10th graders, although no scientific study has shown that it is an effective performance-enhancing drug. Amphetamines and similar compounds may be the most widely abused drug in baseball; recently, they have come under increased scrutiny in sport. Erythropoietin is a highly effective aerobic enhancer that has been linked to multiple deaths in cyclists and other endurance athletes. The neutraceutical industry, led by supplements such as creatine, ephedra, and androstenedione, remains unregulated by the Food and Drug Administration and has serious issues with quality and side effects. An understanding of these products is essential for the sports medicine practitioner to provide sound, safe advice to the athlete.